Factoring as a Perspective Financial Product of the Modern Market - Mirgaziyanovna Yusupova, Lilia; Arkadevna Kodolova, Irina; Viktorovna Nikonova, Tatyana; Irekovna Agliullina, Madina; Irekovna Agliullina, Zarina (International Journal of Criminology and Sociology, 2022)
The article shows the factoring application feature analysis in Russia. Factoring represents a range of services for manufacturers and suppliers who conduct trading activities on a deferred payment basis, and it is currently one of the fastest growing financial services. In its development, Russian factoring has avoided crises and everything that many other sectors of the Russian economy have suffered from. In particular, the article revealed that in recent years the market has grown due to the seriously increased interest of banks - in a crisis, factoring is the least risky product, and players began to actively promote it. The article describes the advantage of factoring over a close financial service - a loan. In addition, directions for the factoring development in the Russian economy were also formulated. In Russia, factoring has only recently begun to actively develop and become successful among organizations engaged in trading. As for foreign experience, the use of factoring is growing rapidly in Western Europe, the USA and Asia. Also in this research we have analyzed the dynamics of factoring services in Russia for the period from 2010 to 2018. Despite the problems and shortcomings of this financial instrument, it has development prospects that are connected with the stabilization of external economic factors, the exchange rate and increasing of the resource provision of financial institutions.